Gross and net erosion of tungsten in the outer strike-point region of ASDEX Upgrade. (12th January 2016) - Hakola, A; Airila, M I; Karhunen, J; Groth, M; Herrmann, A; Krieger, K; Kurki-Suonio, T; Meisl, G; Oberkofler, M; Neu, R; Potzel, S; Rohde, V
Abstract: We have investigated net and gross erosion of W in the outer strike-point (OSP) region of ASDEX Upgrade with the help of marker probes during low-density/high-temperature L-mode discharges. Post mortem analyses indicate net-erosion rates of 0.04–0.13 nm s −1, with the highest rates measured close to the OSP. Re-deposition was some 30–40% of gross erosion, which is lower than what has earlier been obtained spectroscopically (∼50–60%), possibly due to the special plasma conditions of our experiment and intense flux of W atoms originating from the main chamber. Gross erosion was also estimated by passive emission spectroscopy, and around the OSP the results matched with post mortem data. However, the spectroscopic erosion profile in the poloidal direction was much steeper than the post mortem one. Preliminary ERO simulations have predicted net erosion of the same order of magnitude as experimental results but reproducing the poloidal erosion/re-deposition profiles requires further work.